Prevalence of Posttraumatic Stress Disorder and Depression among the Individuals within Faculty of Dentistry, who Experienced Earthquake and who did not, and the Relation with Temporomandibular Joint Disorders - Cennet Neslihan Eroğlu; Serap Keskin Tunç; Mesut Işık; Sadi Elasan (Van Tıp Dergisi, 2017)
INTRODUCTION: The present study aimed to investigate the prevalence of Posttraumatic Stress Disorder (PTSD)-depression among the volunteers within the Faculty of Dentistry, both who experienced earthquake and who did not, as well as to evaluate these subjects in terms of temporomandibular disorder (TMD). METHODS: A total of 124 volunteers from the Faculty participated in the study. All of the subjects completed the Research and Diagnostic Criteria/ Temporomandibular Disorders (RDC/TMD) questionnaire (Axis I-II) and the PTSD questionnaire. Data obtained from both questionnaires were evaluated and then the percentage of population sampling was presented. Statistical analysis of data was done by one-way ANOVA and Chi-Square tests using SPSS 12.0 Windows program. RESULTS: The study comprised 62 subjects that experienced earthquake and 62 subjects that did not, of whom 66 were female and 58 were male with the mean age of 22.76 years. The sign of PTSD was determined in 12.9% and depression was determined in 38.7% of overall volunteers. Myofacial pain was the leading finding (60%) in the subjects with PTSD. Complaints about joint was present in 54.2% of the volunteers that had the signs of depression and the primary (54%) cause of these complaints was osteoarthrosis. Of the volunteers, 48% were psychologically healthy, and 3.3% of these subjects had joint-related complaints. DISCUSSION AND CONCLUSION: It should not be ignored that TMD involves substantial proportion of the subjects having the signs of PTSD and depression. Solving the problems of these subjects by multidisciplinary approach when necessary may be more beneficial for the patients.